(untitled) (Conferencea, 2025)
The article analyzed the results of the pension reform and the results of its development, which began in the years of independence, and made conclusions based on the analysis. Social payments, allowances and pensions received by the people from the state budget and budget funds are of great importance among citizens. Pensions are being paid in full to working pensioners. In this article, we list these and other major changes that have taken place in the pension system in recent years.